OSCILLATIONS IN TW DRACONIS - Zejda, M.; Mikulasek, Z. (Одеські астрономічні публікації, 2007)
TW Draconis is one of the well-know known and studied Algol-like eclipsing binaries. The light variations of TW Dra are caused predominantly by eclipses of the hot main sequence star A8V by the cooler and fainter giant component K0 III. The total primary minimum deep 2.3 mag in B takes 11.5 hours and repeats with the orbital period about 2.807 days. We target our analysis to the study of oscillations in the system of all kind. Combining all available timings of minima we found oscillations of orbital period manifesting in O-C values variations. We speculate they are caused by the mass and angular momentum transfer and the presence of the third body in the system. Our photometric observations confirm also previously revealed oscillations in the light curve. Delta Scuti-like oscillations of the primary component cannot be the only explanation of them, as we found these small light variations also in the bottom of the totality. The complete paper is to be published elsewhere.